Literackie kreacje Tatr i Podhala w wybranych powieściach kryminalnych = Literary visions of the Tatra mountains and Podhale region in selected crime novels - Peroń, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The theme of the Tatra Mountains and Podhale is variously present in detective novels. The mountains are the background of events, giving color to the story or showing a dangerous side of the unpredictable nature in the modernist novel. Literature of the early twentieth century presents Zakopane as a resort where passion is intertwined with death.
Keywords: powieść kryminalna; literatura polska; Tatry; Podhale